Closed-loop Scheduling in a canned food factory. Issue 2 (2020) - Palacín, C.G.; Vilas, C.; Alonso, A.A.; Pitarch, José L.; Prada, C. de
Abstract: This paper addresses the problem of closed-loop operation of scheduling, together with the interaction of control and scheduling, for a class of processes that appear very often in industry: those that combine continuous production lines with parallel batch units that share some resources. The paper presents a novel approach to this problem, including batching and a new type of precedence in the assignment problem. It also considers the effect of shared resources on the duration of the cycle time of the batch units. The approach is illustrated with a real-life example of a canned tuna factory